Gold Nanoparticles with Natural Ingredients as Anti-Aging: A Systematic Review - Agita Dyah Permatasari; Yandi Syukri; Sista Werdyani (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2023)
Aging is a natural process characterized by physiological skin changes. It starts to appear when individuals are in their thirties, making it necessary to use anti-aging products with natural ingredients which are safe even though the penetration is relatively low into the skin. Natural ingredients that can be used are antioxidants that can inhibit aging and can act as bioreductants on gold nanoparticles. Gold nanoparticles can increase penetration into the target cells because of their small size with large surface area. This review article aimed to collect data relating to the development of gold nanoparticles with natural ingredients as anti-aging agents. This review searched through the PubMed and ScienceDirect databases with such keywords as aging, anti-aging, plant extract, antioxidants, and gold nanoparticles. The inclusion criteria were articles in English, available in a full-text version, and published in the last 10 years. Research on the use of natural ingredients as anti-aging agents found that natural ingredients perform better than chemical comparators. Gold nanoparticles are also reported to have been widely used in anti-aging products. Their activity is even better given the low IC50 value and a higher percentage of inhibition compared to those of the extracts without nanoparticle modification. It is reported that gold nanoparticles with natural ingredients as anti-aging agents have a better effect as opposed to purely natural ingredients.